A queer geography of a school: Landscapes of safe(r) spaces - Mel Freitag (Linköping University Electronic Press, 2013)
What does it mean to queer a schooled space? When queers are physically visible in schools, how does that change the power relations and relationships within it? Researchers in the field of Human Geog-raphy have explored physical spaces that are "queered" - the gay ghettos - such as the gay bar, neighborhood, or city. While celebrating these gay spaces, and markers such as the safe space triangle sticker that allies in schools in the USA utilize to mark their offices as places where LGBTQ (lesbian, gay, bisexual, transgender, queer/questioning) students can "go" to feel comfortable, or at least not bullied, that does not always mean that queers feel safe(r) in those spaces. Also, if one space is marked safe, what happens to the other unsafe spaces? Do they stay intact, and if so, is that to the detriment of all students? Therefore, it is imperative also to define what a safe or safe(r) space is, and then why they should exist at all. According to a recent nationwide survey conducted by Joseph Kosciw, Emily Greytak, and Elizabeth Diaz, nine out of ten LGBTQ-identified youth state they have been harassed and bullied in their schools. This is unacceptable. One option in particular for queer subjects is to construct, live, and utilize these "queered" cities, neighborhoods, and schools. A physically separated "gay space" could be a countersite for other, more privileged landscapes and narratives. For example, geographer Dereka Rushbrook takes Michel Foucault's idea of "heterotopias" and defines it as "places that hold what has been displaced while serving as sites of stability for the displaced", which I will use as a framework in this article. Much of the literature on queer geogra-phy has been on isolated or commercialized spaces, neighborhoods, cities, workplaces, bath houses, media, drag shows, sex workers, and more recently on immigration, transnational politics, public health, and globalization. The level of inclusivity of a school, for example, is traditionally a space that holds potential economic and social power for underrepresented students, including but not limited to queer-identified individuals. Queering